Pencegahan Stunting melalui Pemberian ASI Eksklusif di Indonesia: Pendekatan Meta-Analisis: Stunting Prevention through Exclusive Breastfeeding in Indonesia: A Meta-Analysis Approach - Simbolon, Demsa; Putri, Nurlita (Universitas Airlangga, 2024)
Background: The direct cause of stunting in toddlers is nutritional intake, one of which is because babies do not receive exclusive breastfeeding for up to 6 months. Objectives: The purpose of this study is to measure the effect of exclusive breastfeeding on stunting prevention through a meta-analysis approach. Methods: This study uses a meta-analysis approach by searching for research articles from various databases such as Google Scholar, PubMed, and Science Direct. The keywords used are by the Medical Subject Heading (MeSH), namely